The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/1756286421998915
|View full text |Cite
|
Sign up to set email alerts
|

High rates of JCV seroconversion in a large international cohort of natalizumab-treated patients

Abstract: Aims: To retrospectively assess factors associated with John Cunningham virus (JCV) seroconversion in natalizumab-treated patients. Background: Natalizumab is highly effective for the treatment of relapsing–remitting multiple sclerosis (RRMS), but its use is complicated by opportunistic JCV infection. This virus can result in progressive multifocal leukoencephalopathy (PML). Serial assessment of JCV serostatus is mandated during natalizumab treatment. Methods: Patients treated with natalizumab for RRMS at six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Natalizumab is a monoclonal antibody that binds α4β1 and α4β7 integrins located on the surface of lymphocytes preventing them from adhering to the endothelium of the blood-brain barrier thereby decreasing their infiltration of the CNS. The subsequent amelioration of T-cell mediated inflammatory demyelination makes it a highly effective treatment for relapsing-remitting forms of MS ( Dwyer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Natalizumab is a monoclonal antibody that binds α4β1 and α4β7 integrins located on the surface of lymphocytes preventing them from adhering to the endothelium of the blood-brain barrier thereby decreasing their infiltration of the CNS. The subsequent amelioration of T-cell mediated inflammatory demyelination makes it a highly effective treatment for relapsing-remitting forms of MS ( Dwyer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This value is not dissimilar to results from a 2018 meta-analysis of 17 independent natalizumab-treated cohorts of patients with MS, which reported a mean positive seroconversion annualized rate of 10.8% (positivity threshold: index >0.4) . A 2021 registry substudy also reported a similar durable positive seroconversion of 7.3% per year (mean JCV index >1.6) among initially JCV-negative patients treated with natalizumab for RRMS …”
Section: Discussionmentioning
confidence: 99%
“…However, the Swiss product information [3] no longer requires JCPyV-negative patients to have a 'highly active' but rather an 'active' form, though without a change in the indication in the SL [11]. In this context, the yearly rate of seroconversion of JCPyV-negative pwMS of 7.3-10.3% has to be considered [83,84]. In highly active JCPyV-negative pwMS, antibody testing should be performed every three months (no consensus between different centres in Switzerland).…”
Section: Commentarymentioning
confidence: 99%